STRATEGI PEMASARAN TOKO KERAJINAN PERAK HS SILVER KOTAGEDE - , TIARA MAYANG SEKAR; , Fahmi Prihantoro, S.S., S.H., M.A., ([Yogyakarta] : Universitas Gadjah Mada, 2014)
HS Silver is one of silversmithing shop, Yogyakarta. This silver craft store has a huge potential in Kotagede because it has a silver shop workshop tour packages for tourists who come. The purpose of this study was to analyze the marketing strategy of the HS Silver shop silver and supporters know and inhibiting HS Silver shop silver. The author also wants to know what marketing has done for store promotions HS Silver silver Kotagede. In this study the authors obtain the data or information by means of direct observation to the field, then do the documentation to obtain a variety of written documents or data objects as well as images of other photographs that exist in the object, in addition, the authors also conducted interviews with sources, namely Silver and HS staff marketing HS Silver. Store silver Silver HS has some constraints in the face of marketing. In any tourism marketing are common constraints, but these constraints can be overcome. For customer convenience HS Silver should still give priority to the user in the face of the customer.